2020
DOI: 10.1111/anu.13122
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses of juvenile GIFT strain of Nile tilapia ( Oreochromis niloticus ) to dietary L‐tryptophan supplementation

Abstract: A 60‐day indoor feeding trial was conducted to evaluate the effects of dietary tryptophan supplementation on growth performances, whole‐body chemical composition, expression of muscle growth‐related genes (MyoD, myogenin and myostatin), and haematological and biochemical responses of juvenile genetically improved farmed tilapia (GIFT). Five corn–soy‐based isonitrogenous and isoenergetic diets were formulated to contain graded levels of dietary tryptophan (2.6, 3.2, 3.7, 4.2 and 4.8 g/kg of diet). Each diet was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…When fish is subjected to stress, in order to resist from stress, more glucose is produced as demonstrated in rainbow trout (Lepage et al, 2002) and common carp (Hoseini & Hosseini, 2010). The dietary supplementation of tryptophan has been reported to reduce stress, and therefore, reduced glucose level in Nile tilapia (Zaminhan et al, 2018) and GIFT tilapia (Prabu, Felix, Uma, Ahilan, et al, 2020) was observed compared with tryptophan‐unsupplemented diets, which justify reduced glucose content in the present study of the fish fed tryptophan‐supplemented diets.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…When fish is subjected to stress, in order to resist from stress, more glucose is produced as demonstrated in rainbow trout (Lepage et al, 2002) and common carp (Hoseini & Hosseini, 2010). The dietary supplementation of tryptophan has been reported to reduce stress, and therefore, reduced glucose level in Nile tilapia (Zaminhan et al, 2018) and GIFT tilapia (Prabu, Felix, Uma, Ahilan, et al, 2020) was observed compared with tryptophan‐unsupplemented diets, which justify reduced glucose content in the present study of the fish fed tryptophan‐supplemented diets.…”
Section: Discussionsupporting
confidence: 50%
“…The –AA diet was formulated using plant‐based ingredients without supplementation of crystalline amino acids. The balanced diet (BD) was formulated based on the findings of our previous studies (Prabu et al, 2019; Prabu, Felix, Uma, Ahilan, et al, 2020; Prabu, Felix, Uma, & Praveenraj, 2020) with supplementation of DL‐methionine, L‐lysine, L‐tryptophan and L‐arginine. The other diets were formulated by the deletion technique, in which the BD was diluted with cassava starch resulting in a reduction in each amino acid, such as methionine (‐Met), lysine (‐Lys), tryptophan (‐Trp) and arginine (‐Arg) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematological and biochemical parameters are widely used as an indicator of health and physiological status of fish (Zhou et al, 2005). Haematological parameters such as Hb, Ery, Leuk, Ht, MCV, MCH and MCHC are representing the immunity response of host fish (Prabu et al, 2020). Blood lipid and glucose levels were associated with lipid metabolism of body and glucose metabolism as well as nutrient utilization and liver health of animals, respectively (Zhao, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Haemato-biochemical parameters are an important indicator which reflects health and physiological status of fish (Zhou et al, 2005). Haematological parameters such as Hb, WBC, RBC, haematocrit, MCV, MCH and MCHC are representing the immunity response of host fish (Prabu et al, 2020). The present study revealed that complete replacement of fish meal protein with SWP and BSWP had no influence on the haematological parameters in GIFT tilapia.…”
Section: Discussionmentioning
confidence: 50%